Moyshe Kulbak's and Zalman Shneour's Vilnius: Poetic Reality versus Gloriours Contruct - Lempertienė, Lara (Colloquia, 2021)
During the interwar period, many attempts were made to perceive and interpret the legacy of Jewish Vilnius, both in the city itself and abroad. Many of the images of the city created in that period betray nostalgic and half-mythological features, even while they present a living and breathing Jewish environment. This essay is a comparative case study of two literary texts that might provide some answers to these questions. One is the Hebrew poem Vilna by Zalman Shneour (1919), and the other is the Yiddish poem ‘Vilne’ by Moyshe Kulbak (1926). Each poet, the paper argues, set opposing goals for himself: for Shneour, it was creating an ode to a legendary centre of Jewish learning and spirituality; while Kulbak attempted to capture the pulse of the actual city that he lived in. Accordingly, Shneour essentially reiterated every traditional rhetorical trope of Jewish Vilnius, without creating a new poetic vision of it; whereas Kulbak used the potential of modernised Yiddish and Expressionist poetics to paint a vibrant and exciting portrait of the city. However, after the trauma of the physical loss of Jewish Vilnius during the Second World War, it was Shneour’s stylistic approach and depiction of the city that would prevail.
Keywords: Moyshe Kulbak; Zalman Shneour; image of Vilnius